Abscisic Acid Improves Linoleic Acid Accumulation Possibly by Promoting Expression of EgFAD2 and Other Fatty Acid Biosynthesis Genes in Oil Palm Mesocarp - Shi, Peng; Hua, Wei; Htwe, Yin Min; Zhang, Dapeng; Li, Jun; Wang, Yong (Frontiers in Plant Science, 2021)
Abscisic acid (ABA) plays an important role in fruit development. However, the effect of ABA on fatty acid biosynthesis in oil palm is still unknown. In this study, ABA treatments (CK, A1–A4) were applied to oil palm fruit at 16 WAP (weeks after pollination) and fatty acids in the mesocarp at 24 WAP were analyzed by GC-MS. Results showed that linoleic acid content under treatment A2 (20 μM ABA) was significantly higher (slightly increased by 8.33%) than the control. Therefore, mesocarp samples of A2 and the control at 16, 20, and 24 WAP were sampled for RNA-Seq. KEGG pathway enrichment analysis showed that 43 genes were differentially expressed in the fatty acid biosynthesis pathway, of which expression of EgFAD2 (unigene 105050201) under 20 μM ABA treatment was 1.84-fold higher than in the control at 20 WAP. Further sequencing analysis found that unigene 105050201 had more ABA-responsive elements (ABRE), complete conserved domains, and C-terminal signaling motif among threewo FAD2 copies. Furthermore, WGCNA and correlation analysis showed co-expression of EgFAD2 (unigene 105050201) with transcription factors (TFs) (WRI1, AP2-EREBP, bZIP, bHLH, C2C2-Dof, MYB, NAC, and WRKY) and , ABA signaling genes (PYR, PP2C, SnRK, and ABI5) and other genes involved in fatty acids biosynthesis (FATA, FATB, LACS, SAD, Oleosins, and so on). These results indicated that ABA treatment promoted the expression of FAD2 and other genes involved in fatty acids biosynthesis, which possibly resulted in the accumulation of linoleic acid. This study will be helpful for understanding the possible mechanisms through which ABA affects fatty acid biosynthesis and their accumulation in the mesocarp of oil palm.